Culture and the elicitation, experience, and expression of envy - TAN, Yi Wen (Institutional Knowledge at Singapore Management University, 2016)
Envy, generally perceived as a universal emotion, may be elicited, experienced, and expressed differently across cultures. This chapter discusses the cultural similarities and differences with regard to the elicitation (i.e., whether envy is felt), experience (i.e., whether and how feelings of envy are reduced or transformed into other emotional experiences), and expression (i.e., displays and behaviors) of envy. We examine how envy differs across two cultural dimensions: individualism/collectivism and horizontal/vertical, and how these differences influence individual, interpersonal, and group outcomes in organizational settings. In particular, we propose that cultural differences in envy influence organizational outcomes such as job satisfaction and performance, fairness perceptions, citizenship and counterproductive work behaviors, leader-member exchange (LMX), and group cooperation/competition.